UPAYA PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG PENGGUNAAN AROMATHERAPY UNTUK MENGURANGI NYERI PERSALINAN - Yunika, Regina Pricilia; Yadul Ulya; Siskha Maya Herlina (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
Childbirth is the process of expelling a fetus that occurs in a full-term pregnancy, spontaneous birth with a posterior presentation without complications for the mother and fetus. During childbirth, the mother feels pain which can interfere with comfort during contractions. Labor pain appears in the first stage of the active phase. Methods for reducing pain due to childbirth can be done using pharmacological and non-pharmacological methods. Non-pharmacological treatment of labor pain can be treated with aromatherapy because it is believed to be a complementary therapy to reduce the intensity of pain, namely with essential oils derived from the fragrant smell of plants to reduce health problems, the smell has a calming effect on the brain during labor. Objective: to increase pregnant women's knowledge about the use of aromatherapy to reduce labor pain. Method: counseling, discussion, question and answer, as well as pretest and posttest carried out in Geguntur Village, Jempong Baru Village, Sekarbela District, Mataram City on August 8 2023. Results: there was an increase in the knowledge of pregnant women who had good knowledge by 30.8%, namely from 61.5% to 92.3%. Conclusion: there is an increase in pregnant women's knowledge about the use of aromatherapy to reduce labor pain after receiving health education.